Canine-Assisted Therapy and Quality of Life in People With Alzheimer-Type Dementia: Pilot Study - Sánchez-Valdeón, Leticia; Fernández-Martínez, Elena; Loma-Ramos, Sara; López-Alonso, Ana Isabel; Bayón Darkistade, Enrique; Ladera, Valentina (Frontiers in Psychology, 2019)
Background: With the aim of improving the quality of life of people with Alzheimer’s disease, primarily as regards behavioral and psychological symptoms, we implemented canine-assisted therapy in a group of people with this disease. Methods: We conducted a quasi-experimental study, with a simple pre-post case series design. Participants comprised 10 Alzheimer’s day care center users presenting severe or very severe cognitive decline. The measurement instrument employed was the Quality of Life in Late-Stage Dementia (QUALID) scale. Results: By the end of the therapy, 100% of participants showed an improvement in physical, behavioral, and psychological aspects. The total scores of the QUALID scale for the three different evaluation times (before the therapy and 6 and 12 months after starting) after the canine-assisted therapy intervention were smaller and less dispersed. The total score for the QUALID scale decreased significantly (p <0.05) at 6 and 12 months after starting therapy. An analysis by item revealed that the scores of all of them fell during the course of the therapy. Discussion: Our study provides evidence of the significant benefits of canine-assisted therapy for quality of life in people with Alzheimer’s disease.